Judith - Gera, Deborah Levine (Commentaries on early Jewish literature (CEJL), 2014)
"This volume includes a new translation and a detailed verse-by-verse commentary, which touches upon philological, literary, and historical questions. The extensive introduction discusses the work's date, historical background, and original language, biblical and classical influences, and the relation between feminism and theology in the work."